Comparison of the protective effect of the upper zone of the growth plate and unique cartilage matrix-associated protein with hyaluronic acid and corticosteroids on an experimental rat osteoarthritis model - Cemil Emre Gökdemir,; Hamza Malik Okuyan,; İhsan Karaboğa,; Menderes Yusuf Terzi,; Aydıner Kalacı, (Archives of Rheumatology, 2024)
Objectives: This study sought to compare the protective effect of the upper zone of the growth plate and unique cartilage matrix-associated protein (UCMA) with hyaluronic acid (HA) and corticosteroids (CS) in a rat model of osteoarthritis (OA). Materials and methods: In the experimental animal study, 40 adult male rats were randomly assigned into five groups: control, monosodium iodoacetate (MIA) + vehicle (MIA+V), MIA+HA, MIA+CS, and MIA+UCMA. The OA model was induced by an intra-articular MIA injection to the right knee, and intra-articular injections into the right knee were performed on the treatment groups seven times every three days for 21 days. The knee joints were taken for histopathology and immunohistochemistry (IHC) analyses after the rats were sacrificed. All sections were stained with hematoxylin-eosin, safranin O and fast green FCF, and toluidine blue, and bone morphogenetic protein 2 (BMP-2) and nuclear factor-kappa B (NF-κB) expressions were analyzed with IHC. The Mankin scoring was utilized to determine the histopathological changes in the joint tissues. Results: Mankin score was significantly higher in the MIA group compared to the control group. Histopathologically, in the UCMA-, HA-, and CS-treated groups, degenerations in the articular cartilage were milder than in the MIA+V group. Mankin score was found to be decreased significantly in the UCMA-, HA-, and CS-treated groups compared to the MIA group. Furthermore, IHC analyses revealed that NF-κB and BMP-2 expressions elevated in the MIA-induced OA model, while they were downregulated after UCMA, HA, and CS treatments. Conclusion: Our data revealed that UCMA could be used as a potential protective molecule in the prevention and treatment of OA. Furthermore, the protective effect of UCMA was similar to HA and CS, and its possible beneficial roles against OA may be linked to the reduced BMP-2 and NF-κB levels. Further experimental research would make significant contributions to a better understanding of the therapeutic effect of UCMA on degenerative cartilage tissues.